Competitiveness of Gross Regional Domestic Product and Its Effect on Economic Development in Palopo City, South Sulawesi Province - Kadir, Abd; Ilham (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The research aims to analyze the sub-sectors which are the basis of the economy and the competitiveness of the Gross Regional Domestic Product of the City of Palopo and to analyze the Effects of Economic Growth on the Economic Development Index of the City of Palopo, Province of Sulawesi. This research is a descriptive study with a quantitative approach. The data needed in this study are secondary in the form of a time series from 2011 to 2021. This research uses the documentation method from the Central Bureau of Statistics and other related agencies to collect data and information. The techniques used are Location Quotient analysis, Klassen typology, Shift Share, and regression. The findings of this study are that Palopo City has an economic base of electricity, gas, and clean water, Water Procurement, Waste Management, and Recycling, Construction, Trade, Hotels, and Restaurants, Transportation and Warehousing, Financial and Insurance Services Real Estate, Government Administration, Defense, and Compulsory Social Security, Health Services and Social Activities, Other Services. Even though the competitive sub-sectors in Palopo City are the processing industry, gas, electricity and clean water, commerce, hotels, restaurants, transportation, and warehousing, this research also concludes that economic growth in Palopo City does not influence Human Development Index.